(untitled) (Applied Biological Research, 2012)
Chlorophytum borivilianum, due to the presence of high valued industrially important steroidal saponins in its roots, has attracted pharmacological societies worldwide and motivated the farmers of arid and semi-arid zones to cultivate this medicinal herb on commercial scale. However, drought stress is a major abiotic constraint in the successful cultivation of this crop in these areas. One possible way to enhance its production is to improve its drought tolerance through arbuscular mycorrhizal symbiosis. The mechanism by which mycorrhizal symbiosis protects the plants against reactive oxygen species, induced by drought stress, is investigated by evaluating the activity of a set of antioxidant enzymes in relation to different mycorrhizal inocula at various growth stages. The influence of three mycorrhizal inocula viz., Glomus fasciculatum, G. intraradices and G. mosseae on superoxide dismutase, catalase, glutathione reductase, glutathione-s-transferase, polyphenol oxidase and peroxidase enzyme activities were evaluated in well-watered and drought stressed conditions. The result revealed that the entire mycorrhizal plant materials showed higher drought tolerance effect than non-mycorrhizal ones by enhancing antioxidant enzyme activities. Antioxidant activities were more at 180 days of crop harvest. Therefore, it is recommended to harvest C. borivilianum roots at 180 days crop age. Mycorrhizal drought-stressed roots showed significantly higher anti oxidant activities than the well-watered conditions. Thus, it can be assumed that higher antioxidant activities in roots of mycorrhizal plants might have contributed to alleviate the oxidative damage to biomolecules. The cultivation of C. borivilianum with arbuscular mycorrhizae in arid zone, therefore, can be a value addition against drought stress.